Reflective lines to think about the body epistemic unit in interface with the care carried out in nursing - Barbosa, Loeste Arruda (2020)
This academic essay focuses in the knowledge production on nurse domain, which appoint investigated objects of the body and nursing care. In this sense, reflections seek to answer emerges the following objective: reflect about body and nursing care. It’s about a theoretical study, exploratory and with descriptive character, organized in two reflective lines that verse, respectively, about the psychoanalytic bases, which originates a new thinking line for body, and the corporeality in nursing care. In synthesis, the psychoanalysis view of the body in the generation of nursing care invites the understanding, not only as a biological element or diseases container. The reflections putted allowed to conclude that the epistemic unity of body do not resumes to anatomic restricted readings. Stepping into psychoanalytical readings, social and philosophic are thoughts lines that contains possible applications to nursing singular care, unabridged, in favor of human basics necessities of clients in health and diseases situations.